Knowledge and attitudes on anemia and menstrual health among Malaysian female university students - Kai Ting Mok; Satvinder Kaur; Yee-How Say; Siti Sabariah Bahari; Chirawat Paratthakonkun; Trias Mahmudiono; Nurliyana Abdul Razak (Scientific Reports, 2024)
Abstract Anemia is a significant public health concern, particularly among young female adults due to its potential impact on reproductive health. This study investigated the association between anemia-related knowledge, attitudes, menstrual health, and anemia status among Malaysian university students. This was a cross-sectional study named “SCARF” - Study to Combat Anemia - Research for Female Students, involving 674 university students in Malaysia. Anemia status was determined based on haemoglobin level, while knowledge, attitude and menstrual health were measured using validated questionnaires. The mean menarche age of students in this study was 12.1 ± 1.21 years. Students who were anemic had significantly longer menstrual cycle duration (P = 0.034) and more days with heavy flow (P = 0.038). Most students had poor knowledge (44.5%) and attitudes (84.1%) towards anemia. Students with good knowledge were 1.1 times more likely to have better anemia status compared to those with poor knowledge (95% CI: 1.0–1.2, P = 0.049). This study highlighted a lack of practical application of the knowledge to dietary habits. Collaborative efforts between educators and healthcare providers are crucial in developing a comprehensive strategy, such as interventions to prioritise educational initiatives and practical support to enhance overall menstrual health among female students.